2018
DOI: 10.1007/s00417-018-4057-y
|View full text |Cite
|
Sign up to set email alerts
|

Superficial and deep retinal foveal avascular zone OCTA findings of non-infectious anterior and posterior uveitis

Abstract: The deep retinal foveal avascular zone seems to be enlarged in eyes presenting with non-infectious posterior uveitis, both in the presence or absence of macular edema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 17 publications
0
16
1
Order By: Relevance
“…Interestingly, lower V-SO 2 values have also been mentioned in autosomal recessive mode of inheritance in inherited macular dystrophies and more specifically those with STGD phenotype (Bojinova et al 2017). Thus, primarily vascular damages seem to be a characteristic feature for STGD rather than RP which did not present with significant enlargement neither of the superficial, nor the deep foveal avascular zones when excluding patients with macular oedema in order to avoid a strong bias in OCTA analyses (Waizel et al 2018b).…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, lower V-SO 2 values have also been mentioned in autosomal recessive mode of inheritance in inherited macular dystrophies and more specifically those with STGD phenotype (Bojinova et al 2017). Thus, primarily vascular damages seem to be a characteristic feature for STGD rather than RP which did not present with significant enlargement neither of the superficial, nor the deep foveal avascular zones when excluding patients with macular oedema in order to avoid a strong bias in OCTA analyses (Waizel et al 2018b).…”
Section: Discussionmentioning
confidence: 94%
“…In addition, retinal atrophy can occur as a common consequence of retinal capillary dropout. While retinal capillary dropout is a common sequel of retinal vasculitis, it can also occur in cases without obvious presence of retinal vasculitis, for example, in intermediate uveitis [38, 129, 140]. In addition, quantification of the microcirculation in the peripapillary area by OCT-A may be a useful indicator for capillary insufficiency and impairment of ocular blood flow as a long-term complication from inflammation [141].…”
Section: Methodsmentioning
confidence: 99%
“…A prospective observational OCTA study including 74 eyes separated into five groups (posterior uveitis with or without ME, anterior uveitis with or without ME, and healthy controls) showed that, when compared to healthy controls, eyes with non-infectious posterior uveitis with or without ME had a significantly larger deep foveolar avascular zone, and eyes with anterior uveitis and ME had a significantly larger deep and superficial foveolar avascular zone [58]. A possible explanation for these findings might be a peripheral displacement of retinal capillaries as a result of the formation of cystoid spaces or cysts, preferentially leading to non-perfusion areas [58].…”
Section: About the Implementation Of Optical Coherence Tomography Angmentioning
confidence: 99%